Compliance with the consumption of iron and folate supplements by pregnant women in Mafikeng local municipality, North West province, South Africa - Mbhenyane, Xikombiso (Afr Health Sci, 2017)
BACKGROUND: Anaemia due to iron deficiency is recognized as one of the major nutritional deficiencies in women and children in developing countries. Daily iron supplementation for pregnant women is recommended in many countries. The aim of the study was to investigate the factors that contribute to compliance to the consumption of iron and folate supplements by pregnant woman in Mafikeng local municipality, North West Province, South Africa. RESEARCH METHODS: A mixed method of descriptive, exploratory and cross-sectional design was used. Ten clinics were used as a sample frame where 57 pregnant women and 10 health workers were purposefully and conveniently selected. Quantitative techniques were used to collect data on attendance, consumption and nutrition knowledge using the self-reported questionnaire by pregnant women, and structured interview for health workers. Qualitative design was used to conduct in - depth focus-group discussions to gather information on compliance to the consumption of supplements by pregnant women. FINDINGS: The findings of the study revealed good antenatal clinic attendance, availability of supplements and 93% compliance to the consumption of iron and folate supplements. RECOMMENDATIONS: High compliance to the consumption of iron and folate supplements by pregnant women was reported, and this should be reinforced.